Phenotypic characterization of oral mucosa: what is normal? - Valach, Jaroslav; Foltán, René; Vlk, Marek; Szabo, Pavol; Smetana, Karel (Journal of oral pathology & medicine, 2017)
BACKGROUND: Knowledge of the phenotypic pattern of oral squamous epithelium is important in the histopathologic evaluation of lesions including cancer. The literature on normal epithelium is controversial as the phenotype has not been evaluated in samples from completely healthy tissue donors without a history of tobacco and alcohol exposure. METHODS: In this study, we evaluated normal upper lip fornix and gingival mucosa from carefully selected young healthy donors without a history of smoking and alcohol exposure, and keratin types 8, 10, 14, and 17, filaggrin, and Ki67 were investigated in these donors. The results were compared with profile of epithelium from leukoplakia. RESULTS: The results demonstrated that the phenotypic patterns of gingiva and upper lip fornix mucosa were different. Surprisingly, a high proportion of gingival samples exhibited keratin 8 and a suprabasal signal for keratin 14. These patterns were compared with that of human oral leukoplakia, and some phenotypic similarities were noted. CONCLUSIONS: These results demonstrated oral epithelium phenotypic plasticity based on functional requirements of the microenvironment, which can be used in diagnosis.
Keywords: Male; microenvironment; lidé středního věku; keratin; Phenotype; Humans; Middle Aged; senioři; mužské pohlaví; Female; merkel cell; Aged; leukoplakia; ženské pohlaví; ústní sliznice; mladý dospělý; Adult; Young Adult; Mouth Mucosa; filagriny; gingiva; dospělí; lidé; fenotyp; Filaggrin Proteins